2010
DOI: 10.1186/1471-230x-10-99
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum as a complication of emphysematous cholecystitis: Case report

Abstract: BackgroundEmphysematous cholecystitis is a variant of acute cholecystitis which is generally caused by gas-forming organisms. Emphysematous cholecystitis may cause gas spreading within the subcutaneous tissue, peritoneal cavity and retroperitoneum.Case presentationWe present a case of emphysematous cholecystitis in a middle-aged diabetic patient who, postoperatively, presented edema in both flanks and left chest crepitation on palpation, associated with hemodynamic worsening. Computed tomography scan of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 7 publications
(16 reference statements)
0
19
0
6
Order By: Relevance
“…DelgadoPlasencia et al concluded that should be considered as a possible cause of pneumomediastinum [8]. EC should be considered as a possible cause of soft tissue gas gangrene [9].…”
Section: Discussionmentioning
confidence: 99%
“…DelgadoPlasencia et al concluded that should be considered as a possible cause of pneumomediastinum [8]. EC should be considered as a possible cause of soft tissue gas gangrene [9].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The first mentions of EC in the literature were in 1896 by Welch and Flexner. 3 Five years later, Stolz further described the presence of gas in the gallbladder after performing autopsies on three patients. 3,4 In the early 1900s, Hegner described the radiographic features of EC, while Pene postulated that perhaps instead of being a distinct pathology, EC was possibly a variant of acute cholecystitis (AC).…”
Section: Literature Reviewmentioning
confidence: 99%
“…3 Five years later, Stolz further described the presence of gas in the gallbladder after performing autopsies on three patients. 3,4 In the early 1900s, Hegner described the radiographic features of EC, while Pene postulated that perhaps instead of being a distinct pathology, EC was possibly a variant of acute cholecystitis (AC). 1,3 Etiology Emphysematous cholecystitis, also referred to as acute gaseous cholecystitis, aerocholecystitis, clostridial cholecystitis, pneumocholecystitis, or gas gangrene of the gallbladder, has been suggested to be an uncommon outcome of acute cholecystitis, occurring in only 1% to 4% of cases.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations